Kürzungen der Ausgleichsleistungen - Paragraph 45a Personenbeförderungsgesetz (PBefG). - Sterzenbach, Tim (Deutscher Verkehrs-Verl., 2005)
Angesichts der zunehmenden Knappheit öffentlicher Mittel sind in den nächsten Jahren weitere Kürzungen der staatlichen Zuwendungen für den ÖPNV nicht auszuschließen. Die Fähigkeit der Aufgabenträger, Kosten des ÖPNVs zu übernehmen, wird weiter sinken. In diesem Zusammenhang gewinnt die Debatte um eine Kürzung der Ausgleichszahlungen im Ausbildungsverkehr nach § 45a PBefG noch stärker an Bedeutung. Die zur Berechnung der Ausgleichsleistungen zu ermittelnde Kennzahl "Personenkilometer" gilt seit Einführung des § 45a PBefG im Jahr 1977 als "Stellschraube" zur Variation der Finanzmittelzufuhr. difu

1) In view of the growing shortage of public funds, the authorities charged with meeting ÖPNV (Public Local Passenger Transport) costs are increasingly less able to do so. The key to variations in making financial means available to the ÖPNV is the 'passenger kilometer' factor used to calculate compensation payments for services performed in connection with the transport of people who undergo training. 2) In this regard, some Länder have already reduced the validity of travel term passes as a way of varying the application of the 'passenger kilometer' factor. 3) This has led to a proportionally higher than usual cut in the financial means allocated in direct relation to a shorter term pass validity. 4) If both the overall reduction in financial compensation - as per the 'Koch-Steinbrück-Konsenspapier' - and a reduced validity of term passes hits the ÖPNV simultaneously, the adjustment to this changed situation is likely to involve higher tariffs and reductions in the level of service offered. 5) In addition to the ÖPNV carriers' efforts to win more travellers, a review might consider combining the operational and financial responsibilities of ÖPNV carriers and whether this would lead to better ways of calculating the future financial requirements of this sector. difu
Keywords: ÖPNV; Öffentlicher Verkehr; Personenverkehr; Verkehrsunternehmen; Finanzmittel; Kürzung; Ausgleichszahlung; Ausbildungsverkehr; Leistungsträger; Verkehrsangebot; Verkehrsreduzierung; Verkehrstarif; Personenbeförderungsgesetz